Assessment of the antimicrobial activity of Selol - Fitak, Ewa; Wagner, Leopold (Journal of Stomatology, 2017)
Introduction: The modern techniques of caries prevention are multidirectional, related to elimination or reduction of the etiological agents influence. One of the commonly recommended methods is the use of chemical substances that limit the proliferation of acid forming bacteria. Aim: The aim of the study was to assess the activity of 5% Selol on the standard strains of the Streptococcus mutans and the Streptococcus sobrinus bacteria. Material and methods: During the research the microbial susceptibility to Selol was assessed using the disc-diffusion method, the MIC level was established with the use of the double dilution method. The assessment of the microbial survival rate of the bacteria exposed to MIC concentration of Selol was performed. Results: The obtained results indicate that Selol can inhibit the growth of the tested bacteria cultures, and the inhibiting reach is considerably bigger for the Streptococcus sobrinus (p=0.001) strain than for the Streptococcus mutans strain. It was established that 0.63% concentration is sufficient to inhibit the growth of Streptococcus sobrinus, and in the case of Streptococcus mutans the MIC value began at the concentration of 1.25%. During the assessment of the microbial survival rate, 10-times less colonies were observed in the Selol samples than in the control test tubes. Conclusions: Based on the bacteriological examinations conducted it was proved that Selol can inhibit cariogenic Streptococcus mutans and Streptococcus sobrinus bacteria growth. The promising results presented in the article encourage further research and give hope for the possibility of using Selol in caries prevention in the future.